Near‐Field Nano‐Optical Imaging of van der Waals Materials - Kwon, Soyeong; Kim, Jin Myung; Ma, Peiwen J.; Guan, Weilin; Nam, SungWoo (Advanced Physics Research, 2023)
2D van der Waals (vdW) materials are emerging as the next generation platform for optical and electronic devices with their wide coverage of the energy bandgaps. The strong light–matter interactions in 2D vdW layers allow for exploring novel optical and electronic phenomena such as 2D polaritons exhibiting ultrahigh field confinement, defects‐induced new quantum states, and strain‐modulated quantum confinement of 2D excitons. Far‐field optical imaging techniques are extensively used to characterize the 2D vdW materials so far, however, subdiffraction spatial resolution is required for comprehensive investigations of 2D vdW materials of which physical properties are greatly influenced by local defects and strain. This article aims to cover historical advances, fundamental principles, and distinct features of emerging near‐field optical imaging techniques: scattering‐type scanning near‐field optical microscopy, tip‐enhanced Raman spectroscopy, tip‐enhanced photoluminescence techniques, and photo‐induced force microscopy. The recent developments toward spectroscopic analysis of near‐field imaging and applications for unveiling unique properties of 2D polaritons, nanoscale defects, and mechanical strains in 2D vdW materials, are also discussed. This review article provides an understanding of emerging near‐field imaging techniques and suggests prospective applications for exploring 2D vdW materials.